Effect of Curing conditions on the Compressive Strength of Spent Fluid Catalytic Cracking Catalyst (SFCCC)-based Geopolymers - Ruiz G. (2019)
This research evaluates the effect of the curing conditions on the mechanical properties of geopolymers containing spent fluid catalytic cracking catalyst (SFCCC) generated as a waste by the Peruvian oil-refinery industry. For this purpose, two curing conditions were evaluated: i) sample sealing during oven curing to avoid water loss, and ii) the time before curing (pre-curing time or delay time, before heating). The curing temperature was varied from 25°C up to 100°C. The performance of samples was assessed measuring the compressive strengths and the bulk densities. The results reveal that there are optimal curing conditions associated with the higher compressive strength of the SFCCC-based geopolymers. This optimal condition occurred when water loss was reduced by sealing, and samples were allowed to rest before curing (pre-curing). These two conditions assured not only a higher compressive strength but also a denser and more homogeneous product. The results indicate that the higher compressive strengths (up to 34.5 MPa) and bulk densities (up to 1.6 g/cm3) were obtained when the specimens were sealed with plastic bags during the curing process to avoid moisture loss and when they were subjected to a pre-curing period of 24 hours before heating in an oven at 50°C for 1 day followed by curing at room temperature for 6 days. © Published under licence by IOP Publishing Ltd.